Transforming the Conversation: What Is Liberation and from What Is It Liberating Us? A Critical Response to “Transforming Encounters and Critical Reflection: African Thought, Critical Theory, and Liberation Theology in Dialogue” - Justin Sands (Religions, 2018)
The Religions special issue, “Transforming Encounters and Critical Reflection: African Thought, Critical Theory, and Liberation Theology in Dialogue,” addresses the concern over the present postcolonial context in which African persons and societies find themselves. The issue attempts to gain a further understanding of this context through a dialogue between these three disciplines, but what emerges from this attempt? As a critical response to the issue as a whole, this article will reveal that each author presents different yet converging perspectives on the questions: ‘what is liberation and from what are we being liberated?’ This article begins by phrasing this question through Frantz Fanon’s critique on the postcolony, where he sees that the same logic—what Schalk Gerber’s article calls ‘the logic of the colonizer’—is still employed in the postcolony. This article unpacks the entanglement created by this logic and how each author addresses it in different ways. Importantly, this is not a review of each article; rather, it seeks to reveal the narrative created by this interdisciplinary dialogue in order to further the conversation on oppression and liberation in an African context. In so doing, it reveals how each author addresses the concept of liberation or freedom and where they partially (or perhaps provisionally) agree that liberation entails embodied communal responsibility as being-with others, the importance of transparent dialogue, the need for new rationalities to enter the discussion of African self-determination, while also highlighting the dangers of appropriating these new rationalities when bringing them into an African context or when moving theory into praxis.